Features of Multicultural Education in the Modern School Education in Canada - Olha Svyrydiuk (Pedagogical Discourse, 2013)
The pre-conditions of multicultural education in the modern school education in Canada are considered in the article; three stages of evolutionary development of multicultural education in Canadian schools are distinguished.  An overview of multicultural education in the modern school education in Canada is presented; the tasks of contemporary multicultural education in the modern school education are singled out. Key signs of implementation of multicultural education in schools in Canada are characterized; the peculiarities of teachers’ work in classes with students of different ethnic origins are outlined; the specific features of the introduction  multicultural education in Canadaian education institutions particularly in province Ontario are highlighted.